Building Brighter Brains: Inclusive Mathematics Learning with Media and Constructivist Strategies to Enhance Focus and Recall - Pandia, Weny Safitri S.; Laudra, Asyanti; Caw, Sonia (CV. Bimbimbingan Belajar Assyfa, 2024)
Particularly in inclusive classrooms, the level of teacher assistance also affects student achievement. The issue encountered in mathematics education is the utilization of a unidirectional learning approach, resulting in a lack of meaningful learning. In the classroom, teachers typically exert control over teaching and learning activities. Mathematics is the sole topic that is studied consistently from kindergarten through college. The objective of this study is to elucidate the significance of employing constructivism-based mathematics learning materials for students in inclusive educational institutions. The research methodology employed is a literature review, namely by curating a collection of publications about the research topic through electronic search engines in reputable journals published over the past decade, specifically from 2013 to 2023. The original search was centred around the keywords